Apical Functionalization of Tribenzotriquinacenes. Issue 35 (22nd July 2016) - Dhara, Ayan; Weinmann, Joshua; Krause, Ana‐Maria; Beuerle, Florian
Abstract: The introduction of one alkyne moiety at the central carbon atom of the tripodal tribenzotriquinacene scaffold allows easy access to a great variety of apically functionalized derivatives. The spatially well‐separated arrangement of different functional units on the convex face and outer rim was further proven by single‐crystal X‐ray studies. Subsequent modifications that feature a general protecting group‐free strategy for the demethylation of protected catechols in the presence of a terminal alkyne group, an azide–alkyne Huisgen cycloaddition, and Sonogashira cross‐coupling reactions showcase the high synthetic potential of this modular approach for tribenzotriquinacene derivatization. Abstract : Reaching the top : The introduction of an alkyne moiety at the central carbon atom of the tribenzotriquinacene scaffold provides an anchor group for the facile apical functionalization of bowl‐shaped molecules. Subsequent reactions, such as an azide–alkyne cycloaddition, Sonogashira cross‐coupling reaction, or selective demethylation at the outer rim, were performed to highlight the synthetic potential of this approach (see picture).